Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1177/1745506519846747
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and challenges of a culturally relevant intervention to improve attitudes to aging

Abstract: Objectives: Attitudes to aging have been linked with important health outcomes. It is unclear whether interventions to improve attitudes to aging are effective across cultural contexts. This study investigated the efficacy of an intervention among women of either Australian or Chinese backgrounds. Methods: Among 96 women who provided baseline measures, 86 attended a single, 90-min group session on either healthy aging or healthy diet. Measures of three domains of attitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…The scores obtained were similar to those obtained in other studies on nursing students in Europe and the United States [ 39 , 40 , 41 ], and slightly higher than in Asian students [ 42 ]. The cultural background seems to be an important factor, as other studies have also reported more negative scores in Asian countries compared to western countries [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…The scores obtained were similar to those obtained in other studies on nursing students in Europe and the United States [ 39 , 40 , 41 ], and slightly higher than in Asian students [ 42 ]. The cultural background seems to be an important factor, as other studies have also reported more negative scores in Asian countries compared to western countries [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Attitudes towards aging seem to be a promising area of research regarding interventions on successful and healthy aging (Kunuroglu & Vural Yuzbasi, 2021;Laidlaw, 2010;Segel-Karpas et al, 2022;Yamada et al, 2015). Seah et al (2019) found that short, culturally inclusive interventions were effective in enhancing attitudes towards aging. Interventions targeting attitudes towards aging could be a potential clinical approach for improving quality of life in older adults.…”
Section: Discussionmentioning
confidence: 99%